Detection of Chronic Obstructive Pulmonary Disease among Smokers Aged ≥40 years Attending Primary Health Care Centers in Baghdad-AL-Karkh and AL-Resafa - Abd Ala, Isra A.; Mousa, Nada Abdul Wahhab; Al-Lami, Faris (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Chronic obstructive pulmonary disease causes permanent morbidity, premature mortality and great burden to the healthcare system. Smoking is it’s most common risk factor and Spirometry is for diagnosing COPD and monitoring its progression. Objectives: Early detection of chronic obstructive pulmonary disease in symptomatic smokers’ ≥ 40years by spirometry. Methods: A cross sectional study on all symptomatic smokers aged ≥ 40 years attending ten PHCCs in Baghdad Alkarkh and Alrisafa. Those whose FEV1/FVC was <70% on spirometry; after giving bronchodilator, were considered COPD +ve. Results: Overall, airway obstruction was seen in 206(46.8%). It is significantly associated with increase age (50-y), more in male and increase with increase duration and amount of smoking Conclusions: COPD was prevalent among men and women. Early diagnosis of COPD is good for both patient and community. Routine spirometry is an easy way for screening and identifying asymptomatic patients. Before adoption of spirometry Cost-effectiveness is needed.